Occupational Safety Analysis of Coal Hauling Activities Using the Job Safety Analysis (JSA) Method at PT Lematang Coal Lestari - Wanda Elisa; Aris Susilo; Rodiyah Nursani (Technema: Journal of Intelligent Engineering and Computing, 2026)
Coal hauling is a critical stage of mining operations with potential accident risks arising from heavy-equipment interaction, haul-road conditions, human factors, and the work environment. This study aims to analyze occupational safety in coal hauling activities using the Job Safety Analysis (JSA) method at PT Lematang Coal Lestari (LCL). An empirical descriptive-qualitative research design was employed, with data collected through field observations, interviews with operators, supervisors, and SHE personnel, and company documentation. The analysis involved mapping work stages, identifying potential hazards, assessing risk levels based on likelihood and severity, evaluating existing controls, and formulating additional control measures. The findings indicate that hazards were identified in the pre-start inspection, loading, hauling, dumping, and return stages, including vehicle collisions, vehicle rollover, slippery roads, dust, blind spots, excessive speed, and non-compliance with safety procedures. Existing controls include PPE use, daily inspections, toolbox meetings, haul-road maintenance, speed regulation, radio communication, safety signage, and field supervision. The findings demonstrate that JSA provides a structured framework for linking task-specific hazards with operational control measures. Consistent implementation of these controls and periodic JSA updates are required to maintain operational safety and strengthen risk management in coal hauling activities. Continuous monitoring of road conditions and worker compliance is also necessary to address changing operational risks.